2020
DOI: 10.1111/tid.13467
|View full text |Cite
|
Sign up to set email alerts
|

A split strategy to prevent cytomegalovirus after kidney transplantation using prophylaxis in serological high‐risk patients and a pre‐emptive strategy in intermediate‐risk patients: Combining the best of two options?

Abstract: Background Cytomegalovirus (CMV) remains an important challenge after kidney transplantation. Current Transplantation Society International Consensus Guidelines recommend antiviral prophylaxis or pre‐emptive therapy for high‐risk CMV‐seronegative recipients with a CMV‐seropositive donor (D+/R−) and moderate‐risk CMV‐seropositive recipients (R+). However, a split strategy according to CMV serostatus is not specifically mentioned. Methods We evaluated a split strategy to prevent CMV infection after kidney transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…A recent study showed that among 40 D+/R− kidney transplant recipients receiving pharmacological prophylaxis for 200 days, the incidence of neutropenia was 53%, 30% had to reduce/discontinue MPA and 35% valganciclovir, with still 15% late CMV infection. In the same study, among 92 R+ patients receiving preemptive therapy, 40% were treated for CMV, with a mean duration of 21 days, and only 5% developed neutropenia [32]. A recent multicenter, open‐label, randomized clinical study showed that the incidence of CMV infection or disease was 11.5% among patients receiving prophylaxis and 39.7% in those receiving preemptive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that among 40 D+/R− kidney transplant recipients receiving pharmacological prophylaxis for 200 days, the incidence of neutropenia was 53%, 30% had to reduce/discontinue MPA and 35% valganciclovir, with still 15% late CMV infection. In the same study, among 92 R+ patients receiving preemptive therapy, 40% were treated for CMV, with a mean duration of 21 days, and only 5% developed neutropenia [32]. A recent multicenter, open‐label, randomized clinical study showed that the incidence of CMV infection or disease was 11.5% among patients receiving prophylaxis and 39.7% in those receiving preemptive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, a total of 75 papers were excluded during either full‐text screening or data extraction. Ultimately, 82 citations 2,6–86 including 65,386 participants met inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 27 studies reported neutropenia incidence 2 , 6,11,14,15,26,30,31,34,36,39,42,44,46–48,51,60,63,64,68,69,75,76,78,81,85 . The absolute neutrophil count (ANC) threshold to define neutropenia varied widely; the majority of the studies ( n = 12) reported neutropenia with a threshold of ANC <1000/μl 2,6,11,15,26,36,44,51,63,75,81,85 followed by a threshold of <500/μl ( n = 8 11,26,34,42,44,60,81,85 ), <1500/μl ( n = 7 26,44,46,60,68,76,81 ), and <2000/μl ( n = 3 64,78,81 ); in 7 studies 14,30,39,42,47,48,69 , a threshold definition was not reported. In 1 study, 31 neutropenia was defined using an International Classification of Diseases, Ninth Revision (ICD‐9) code.…”
Section: Resultsmentioning
confidence: 99%
“…Among 877 studies screened, 154 duplicates and 586 studies were excluded from the title/abstract, leaving 137 studies that included 149 cohorts (115 UP and 34 PET) that were fully reviewed for eligibility by 2 independent authors (Figure 1). Among these 137 studies, 19 UP studies 13,27,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] and 6 PET studies [19][20][21][52][53][54] met inclusion criteria, comprising 993 patients in the UP cohort and 234 patients in the PET cohort. One study that met inclusion criteria was excluded because of variable definitions of CMV disease and overlap of cohorts from the same center in 2 separate publications.…”
Section: Study Selectionmentioning
confidence: 99%